BuyFind

Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071
BuyFind

Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071

Solutions

Chapter 1.4, Problem 72E
To determine

To calculate: The expression (x+h)37(x+h)(x37x)h

Expert Solution

Answer to Problem 72E

  (x+h)37(x+h)(x37x)h=h2+3x2+3xh7

Explanation of Solution

Given information:

Given expression is (x+h)37(x+h)(x37x)h

Formula used:

  (a+b)3=a3+b3+3a2b+3ab2

Consider the expression as (x+h)37(x+h)(x37x)h

Now,

  (x+h)37(x+h)(x37x)h=x3+h3+3x2h+3xh27x7hx3+7xh=h3+3x2h+3xh27hh=h(h2+3x2+3xh7)h=h2+3x2+3xh7

Therefore, simplest form of the expression (x+h)37(x+h)(x37x)h=h2+3x2+3xh7

Have a homework question?

Subscribe to bartleby learn! Ask subject matter experts 30 homework questions each month. Plus, you’ll have access to millions of step-by-step textbook answers!